Aglaia dookoo Grift Fruit Growth and Development of Longkong (Aglaia dookoo Griff.) - Suchanya Chantaksinopas; Suraphong Kosiyachinda (Agriculture and Natural Resources, 1987)
The study on fruit development of longkong (Aglaia dookoo Griff.) was carried out at Bhannara orchard in Su-nghaipadee district, Narathiwat province during April to September 1982. Experimental data showed that over 95% of fruit had 5 carpels. The growth curve from fruit set until maturity was in the single sigmoidal form, and the growth period was 14 weeks. The fruit shape during the growth period up to 13 weeks was global, and changed to spherical appearance a week after. The rind thickness increased after fruit set to the ninth week, then decreased slightly until maturity. The percentage of soluble solids (SS) in fruit juice increased gradually decreased until the fruit became mature with 1% of titratable acids (TA) at week 15. Soluble solids/titratable acids ratio at the week 15 was 18.1. The harvesting period is recommended during week 14 to 16 after fruit set.